The youth employment service - why, what and how - Jenks, Richard, E. (Statistical and Social Inquiry Society of Ireland, 1963)
In Great Britain, at the beginning of this century, it was felt that, as a natural corollary of the greatly increased public expenditure on education, provision should be made for young people and their parents to receive information and advice about the types of employment in which that education might best be used. This feeling led to the passing of two Acts of Parliament, the Education (Scotland) Act, 1908 and the Education (Choice of Employment) Act, 1910, which empowered Local Education Authorities to make arrangements for giving boys and girls assistance with respect to the choice of suitable employment by means of the collection and the communication of information and the furnishing of advice...
Read before the Society, 11 March 1963
Keywords: Education; Training; Youth employment service; Career guidance; Human capital investment; Northern Ireland; 314.15